Alternative route for the synthesis of new derivatives of benzimidazo[2', 1':2, 3] thiazolo[5, 4-d]pyrimidine. (1st September 2015) - Asghari, Tayebe; Bakavoli, Mehdi; Eshghi, Hossein; Shiri, Ali; Ebrahimpour, Zahra
A series of new benzimidazothiazolopyrimidines were synthesised through a route involving successive nucleophilic substitution of 5-bromo-2, 4-dichloro-6-methylpyrimidine with 2-mercaptobenzimidazole and secondary amines, respectively and eventually cyclisation in the presence of KOH in DMF. The structures of the newly synthesised compounds were characterised by their spectral data and elemental analysis.